Antimicrobial, Cytotoxicity and Molecular Docking Study of New Quinoline Schiff Base and its Metal(II) Complexes - Vibhute, B.T.; Aghav, B.D.; More, B.P.; Bellamkonda, R.O.; Patil, S.K. (Asian Journal of Chemistry, 2022)
A new quinoline Schiff base ligand was synthesized by the reaction of 2-hydroxy-7-methylquinolin-3-carbaldehyde and 4-methylbenzene sulfonohydrazide. Synthesized Schiff base further utilized for the formation of stable metal complexes with Cu(II), Ni(II), Co(II) and Cd(II) metal salts and characterized by different spectroscopic techniques i.e. 1H NMR, 13C NMR, FT-IR, UV-visible, ESR, MASS and TGA. The low molar conductance values indicate that synthesized metal(II) complexes were non-electrolytes. The magnetic moment value indicates that Cu(II), Ni(II) and Co(II) complexes were paramagnetic. Further, these compounds were screened for inhibition activity against four bacterial strains, three fungal strains and cytotoxicity against the A-549 and MCF-7 cell lines by using the MTT method. Among the synthesized complexes, metal complexes exhibited excellent anticancer activity against the human lung cancer cell line (A-549). Schiff base and its Cd(II) complex showed good antibacterial activity. Furthermore, molecular docking study shows the significant binding affinity of metal complexes with tubulin protein. Present study proposed that all the synthesized Schiff base metal(II) complexes have excellent biological activity and could be act as potential anticancer agents.